Transcriptional regulation of the human papillomavirus-16 E6-E7 promoter by a keratinocyte-dependent enhancer, and by viral E2 trans-activator and repressor gene products: implications for cervical carcinogenesis. - Cripe, T P (1987)
The transcriptional promoter of the candidate E6-E7 transforming gene region of human papillomavirus (HPV)-16 (P97) was active in transiently transfected cervical carcinoma cells when linked to the HSV-1 tk or bacterial cat genes. Sequences 5' to P97 contain a short enhancer element responding to cellular factor(s) in uninfected human foreskin keratinocytes and in cervical carcinoma cells, but not in human or animal fibroblasts. The E2 trans-activator products of HPV-16 or of the related bovine papillomavirus (BPV)-1 further elevated HPV-16-driven transcripts in co-transfections, and required the presence of E2-binding ACC(N)6GGT cores in cis. A 'short E2' C-terminal repressor gene product (sE2) of HPV-16 or the BPV-1 sE2 repressor not only inhibited viral E2 trans-activation, but also suppressed enhancer response to keratinocytic factors. Suppression by the sE2 products was abolished by deletion of the E2-binding cores in cis or by a mutation in the sE2 DNA binding domain. The keratinocyte-dependent enhancer is likely to contribute to the epithelial cell tropism of HPV-16, and may direct persistent E6-E7 gene transcription in response to cellular factors in cervical carcinoma cells in which the viral E2 genes are inactive.